A cross-cultural comparison of wine consumption and purchasing behaviour in Germany and Hungary - Gergely Szolnoki; Gedeon Totth (Wine Economics and Policy, 2020)
Both the German and the Hungarian wine markets belong to the "old world" European winemaking heritage and each have long winemaking traditions; however, since the 1950s, they have gone through completely different changes as political and economic circumstances greatly influenced the development of these wine markets. This paper, based on a representative survey of 2,000 participants in Germany and 1,500 participants in Hungary, investigates the differences in consumer behaviour and sales channel structures in both countries. The results indicate that, despite some similarities, there are large differences between German and Hungarian wine consumers in not only wine preferences but also in the use of sales channels. The two countries differ especially in the number of heavy drinkers and in the socio-demographic background of wine drinkers. These results shall provide important information and insights for producers and marketers about the wine markets of these two European countries.
Keywords: 330; wine; wine market; consumer behaviour; Hungary; Germany; cross-cultural comparison; sales channels